COVID-19 and the Future of the Hospitality Industry: An Indonesian Case Study on the Industry's Adaptation, Recovery Plan, and Resilience - Khairune Nisa, An Nuur (Ann Publisher, 2024)
With hotels being forced to close and experiencing sharp drops in visitor numbers and revenue, the COVID-19 epidemic has significantly affected the hospitality sector. Diverse adaption techniques have been presented to overcome these issues, like tilting, positioning, and contactless experience. In order to better understand the post-pandemic hospitality industry, this study will examine recovery trends and tactics. Various techniques are employed in qualitative analysis, such as gathering data from sources that provide descriptive information, like industry reports, interviews with stakeholders, and text analysis of relevant publications. The talk covered the hotel industry's supply and demand analysis, adaption tactics used by lodging facilities, and the importance of cooperation amongst stakeholders in ensuring the industry's resilience. The data demonstrate that the pandemic has caused substantial changes in the hospitality sector. However, there is a tremendous chance for recovery due to the expansion of the MICE sector and a rise in domestic travel. Finally, the hotel sector can successfully navigate the future with the appropriate adjustments and good teamwork.